(untitled) (Journal of Management and Social Sciences, 2019)
Social science phenomena are regularly faced with a myriad of debate among which are the issues of conceptualization and perspectives. These differing views come about as a result of differences in the scope, operationalization, methodology, objectives, time or socio cultural context of exiting social science researches. Expectedly, the concept of online political participation on social media in the digital age has also been affected by these debates. Social media has rapidly been adopted as a tool for political participation because online opportunities for such participation have become an important avenue for citizens’ engagement in democracies. Consequently, increasing number of researches are being carried out in this area, thus creating differing views in terms of definitions and perspectives of the phenomena online political participation on social media. As a consequence, this paper attempts to elucidate arguments on these views by reviewing some existing studies in this area with a view to providing a clear understanding of this form of political participation on social media.